CE‐MS for metabolomics: Developments and applications in the period 2010–2012. Issue 1 (3rd December 2012) - Ramautar, Rawi; Somsen, Govert W.; de Jong, Gerhardus J.; Rassi, Ziad El
<x xml:space="preserve">Abstract</x> CE‐MS has emerged as a powerful technique for the profiling of (highly) polar and charged metabolites in biological samples. This review provides an update of the most recent developments in CE‐MS for metabolomics covering the scientific literature from July 2010 to June 2012. The present paper is an update of two previous review papers covering the years 2000–2010 (Electrophoresis 2009, 30, 276–291; Electrophoresis 2011, 32, 52–65). Emerging technological developments used in CE‐MS for metabolomics are discussed, such as the use of novel interfacing techniques for coupling CE to MS. Representative examples illustrate the applicability of CE‐MS in the fields of biomedical, clinical, microbial, plant, environmental and food metabolomics. Concerning targeted and non‐targeted approaches, a comprehensive overview of recent CE‐MS‐based metabolomics studies is given in a table. Information on sample type and pretreatment, capillary coatings and MS detection mode is provided. Finally, general conclusions and perspectives are provided.